Impact of Cultural Differences in Marketing on Buying Behaviour - Anushka Naik; Avantika Sharma (International Journal of Engineering and Management Research, 2021)
Culture and differences in culture across the globe form an important aspect of marketing. One of the biggest factors that is taken into consideration by both marketing analysts and consumers is culture. Cultural Marketing, therefore, has gained importance as a way of marketing and market research. Especially when it comes to international trade and global marketing. The volatile nature of cultures as a concept makes it very difficult to predict the success or failure of a product or service. Cultural differences in marketing, therefore form the fundamental decision-making factors in the international marketing arena. This paper studies the consumers’ perception towards marketing strategies that align with their culture and the subsequent decisions they are likely to take based on these factions. Understanding this psychology is crucial to ensuring that a company can get a good return on its market investments while still generating a profit. Hence understanding the culture of a particular region before entering it is crucial and can play a huge role in the success of the company in that region.